2017
DOI: 10.1111/soru.12160
|View full text |Cite
|
Sign up to set email alerts
|

Rendering the Actually Existing Sharing Economy Visible: Home‐Grown Food and the Pleasure of Sharing

Abstract: Despite the unprecedented attention paid to the sharing economy and despite the growing interest in household food production, the non-market and non-monetised sharing of home-grown food -a social practice at the intersection of these two concerns -has so far largely escaped scholars' attention. The goal of the article is twofold. First, drawing on a large-scale survey (2058 respondents) and four focus groups conducted in the Czech Republic in 2015, the article shows that in the Global North the sharing of hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
68
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(82 citation statements)
references
References 50 publications
7
68
0
7
Order By: Relevance
“…However, as the primary data shows, these practices are quite sustainable, and develop in parallel to the formal market‐based agro‐food system. This finding is in line with the recent shift in understanding post‐socialist informal food practices – from viewing them as need‐driven and poverty‐related strategies to viewing them as alternative food networks free from state interference (Jehlička and Daněk ).…”
Section: Rethinking Large‐scale Agriculture and State Policysupporting
confidence: 79%
See 1 more Smart Citation
“…However, as the primary data shows, these practices are quite sustainable, and develop in parallel to the formal market‐based agro‐food system. This finding is in line with the recent shift in understanding post‐socialist informal food practices – from viewing them as need‐driven and poverty‐related strategies to viewing them as alternative food networks free from state interference (Jehlička and Daněk ).…”
Section: Rethinking Large‐scale Agriculture and State Policysupporting
confidence: 79%
“…While previous studies have assumed a causal link between economic hardship and food self‐provisioning, recent research in the region has demonstrated that these practices play an important role in strengthening social cohesion, environmental sustainability and food re‐localisation. Therefore, they are broadly compatible with – but also transcend – the tenets of alternative food networks (Smith and Jehlička ; Jehlička and Daněk ).…”
Section: Introductionmentioning
confidence: 90%
“…We focused only on the food produced and consumed in a household but an additional proportion of food is obtained as a gift or exchanged by all Czech households regardless of whether they produce food by themselves or not. The share of given or exchanged food is 5% of vegetables, 7% of fruits and 6% of potatoes (see Jehlička and Daněk 2017). This food is also home grown and has positive environmental consequences.…”
Section: Strengths and Limitations Of The Researchmentioning
confidence: 99%
“…As comparative research [32] has shown, food self-provisioning as well as other informal food economies (e.g., foraging [33]) are much more common in Central and Eastern Europe (CEE) than in Western Europe. Given the recent interest in these topics, CEE's long tradition of informal food economies could provide rich learning opportunities for food system scholars [34]. These opportunities to learn, however, have not yet been seized: although there is a considerable body of literature on food self-provisioning in CEE [32,[35][36][37], these writings are rarely related to the current debates on multifunctional urban agriculture, spaces of resistance or environmentally sustainable food systems.…”
Section: Introductionmentioning
confidence: 99%